The influence of population growth and wind on vagrancy in a North American passerine - Zawadzki, L; Veit, R; Manne, L (BiOne Publishing, 2019)
Understanding the causes of vagrancy among migratory bird species is of increasing importance as climate change threatens species' survival. Vagrancy may serve to safeguard populations from environmental change through expansion of their geographic ranges. To dissect underlying causes of vagrancy, we analysed data on occurrence of vagrant Ash-throated Flycatchers Myiarchus cinerascens to the east coast of North America and population growth within their core breeding range, to test to what extent vagrancy is driven by population growth and the production of young that have a proclivity to explore new places. We also tested to what extent vagrancy is related to drift by prevailing winds, through analysis of synoptic weather maps of North America. Our analyses aimed to quantify which factors most strongly influence interannual variation in the number of Ash-throated Flycatchers reaching the east coast of North America. We obtained records of vagrants from ‘North American Birds’, population data from the North American Breeding Bird Survey (BBS), reproductive success from Monitoring Avian Productivity and Survivorship (MAPS) databases, and synoptic weather maps from the NOAA NCEP North American Regional Reanalysis database. We found that vagrancy was predominantly explained by the growing breeding population size as indexed by BBS data. In addition, we found significant effects of annual production of young within the breeding range, as well as three measures of air circulation across North America. Our models indicated an important role of population growth, with additional effects of reproductive success and predominant airflow affecting the incidence of vagrancy. Years of high reproductive success bring larger numbers of Ash-throated Flycatchers to the east, and this number is enhanced when weather conditions are especially favourable.